1999
DOI: 10.1007/s001200050241
|View full text |Cite
|
Sign up to set email alerts
|

Detrusormyectomy (autoaugmentation) in the treatment of hyperreflexive low-compliance bladder

Abstract: After unsuccessful medical treatment of a neurogenic hyperreflexive bladder dysfunction further treatment options are the ileal bladder augmentation, the detrusor-myectomy (bladder auto-augmentation) and the sacral root deafferentation. All techniques lead to a low-pressure bladder with enlarged storage volume. The authors here report about their personal experience with the detrusor myectomy in 62 patients with hyperreflexive neurogenic bladder dysfunction from 1989 until 1998. Indication, surgical technique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Success rates of 33‐94% and 58‐100% have been reported, respectively. Both methods achieve significant increases (>50%) of bladder capacity and decreases in storage pressure (>50%), but at the cost of increased residual urine and need for intermittent catheterisations (45‐75% of detrusor myectomy patients, nearly all AC patients) . Complication rates are low for detrusor myectomy but considerably higher for AC (infections, incontinence, absorption disorders, stones, ileus, secondary malignancy, reservoir rupture, reinterventions) .…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Success rates of 33‐94% and 58‐100% have been reported, respectively. Both methods achieve significant increases (>50%) of bladder capacity and decreases in storage pressure (>50%), but at the cost of increased residual urine and need for intermittent catheterisations (45‐75% of detrusor myectomy patients, nearly all AC patients) . Complication rates are low for detrusor myectomy but considerably higher for AC (infections, incontinence, absorption disorders, stones, ileus, secondary malignancy, reservoir rupture, reinterventions) .…”
Section: Methodsmentioning
confidence: 98%
“…Both methods achieve significant increases (>50%) of bladder capacity and decreases in storage pressure (>50%), but at the cost of increased residual urine and need for intermittent catheterisations (45-75% of detrusor myectomy patients, nearly all AC patients). [63][64][65][66][67][68][69][70][71][72][73][74][75][76] Complication rates are low for detrusor myectomy but considerably higher for AC (infections, incontinence, absorption disorders, stones, ileus, secondary malignancy, reservoir rupture, reinterventions). [73][74][75] Prior pelvic irradiation or extensive bladder fibrosis are contraindications for detrusor myectomy but not for AC.…”
Section: Augmentation Cystoplasty For Drug-resistant Oab/domentioning
confidence: 99%
“…Functional bladder capacity in the animals increased by 43.5%, and there was no statistical difference between the two techniques. They then performed vesicomyotomies (incision) in 12 patients with neurogenic bladder dysfunction and demonstrated a mean increase in capacity of 40% and a mean decrease in leak point pressure of 33% (78,80) . They concluded that detrusor excision offered no advantage over incision.…”
Section: Autoaugmentation 511 Techniques and Resultsmentioning
confidence: 99%
“…Other techniques employ demucosalized, colonic, gastric, and sigmoid tissue to cover the urothelial diverticulum. Some physicians prefer not to cover the myectomized area, assuming that the procedure will reduce overall compliance [32]. A catheter is left in place for 2 to 7 days after the procedure, and a cystogram is performed before the catheter is finally removed.…”
Section: Detrusor Myectomy (Autoaugmentation)mentioning
confidence: 99%